2017
DOI: 10.1002/ajh.24611
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal column myelopathy after intrathecal chemotherapy for leukemia

Abstract: Intrathecal chemotherapy with methotrexate, a folate antagonist, is widely used to treat central nervous system malignancies. The mechanisms underlying methotrexate-induced neurotoxicity are unclear but may be related to increased homocysteine levels. Intrathecal methotrexate-induced myelopathy mimicking sub-acute combined degeneration, with normal B12 levels, has been documented. We examined treatment and magnetic resonance imaging (MRI) characteristics of 13 patients with leukemia who received intrathecal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Finally, intrathecal methotrexate treatment is a well-known cause of cerebral leucopathy and myelopathy of toxic metabolic origin, mimicking subacute combined degeneration 48. Contrast enhancement was rarely reported 49.…”
Section: Genetic and Metabolic Causes Of Medullary Signal Alterationsmentioning
confidence: 99%
“…Finally, intrathecal methotrexate treatment is a well-known cause of cerebral leucopathy and myelopathy of toxic metabolic origin, mimicking subacute combined degeneration 48. Contrast enhancement was rarely reported 49.…”
Section: Genetic and Metabolic Causes Of Medullary Signal Alterationsmentioning
confidence: 99%
“…We finally concluded that the most likely cause is the simultaneous administration of intrathecal MTX and systemic high‐dose MTX during the even cycles. Contrast‐enhanced magnetic resonance imaging (MRI) of the spine, in such cases, may demonstrate T2 hyperintensity as a sign of myelopathy . As a result, we have changed practice during the MTX/cytarabine (even) courses, reversing the sequence of intrathecal chemotherapy to avoid increased risk of neurotoxicity.…”
Section: Anticipated Scenarios Prone To Complicationsmentioning
confidence: 99%
“…Contrast-enhanced magnetic resonance imaging (MRI) of the spine, in such cases, may demonstrate T2 hyperintensity as a sign of myelopathy. 15,16 As a result, we have changed practice during the MTX/cytarabine (even) courses, reversing the sequence of intrathecal chemotherapy to avoid increased risk of neurotoxicity. Therefore, intrathecal cytarabine is administered on day 2 (±2 days) and MTX is administered on day 8.…”
Section: Scenario 3: Concomitant Intrathecal and Systemic Chemotherapymentioning
confidence: 99%
“…The MRI image showed hyperintensity in the posterior column on the T2-weighted image. Vitamin B12 deficiency, nitrous oxide abuse, and intrathecal methotrexate can all produce posterior column T2 hyperintensity [1][2][3]. However, in the setting of leukemia and chemotherapy, intrathecal methotrexate should be suspected as the most likely etiology.…”
mentioning
confidence: 99%
“…The imaging findings of methotrexate-induced myelopathy often resemble that of subacute combined degeneration from B12 and folate deficiency [3]. Time between treatment and development of myelopathy can be weeks to months.…”
mentioning
confidence: 99%